2008
DOI: 10.1104/pp.107.114751
|View full text |Cite
|
Sign up to set email alerts
|

SEUSSandAINTEGUMENTAMediate Patterning and Ovule Initiation during Gynoecium Medial Domain Development    

Abstract: The Arabidopsis (Arabidopsis thaliana) gynoecium, the female floral reproductive structure, requires the action of genes that specify positional identities during its development to generate an organ competent for seed development and dispersal. Early in gynoecial development, patterning events divide the primordium into distinct domains that will give rise to specific tissues and organs. The medial domain of the gynoecium gives rise to the ovules, and several other structures critical for reproductive compete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 53 publications
2
83
0
2
Order By: Relevance
“…It is thus clear that ANT transcription factors are regulated by auxin gradient suggested for auxin-mediated regulation of ANT transcription factor in SE. The ANT is part of a complex and robust molecular system that coordinates patterning signals and cellular proliferation through embryo development [58]. This data indeed provide support for the structural changes in the regulatory sequence of AtSERK1 gene evolved exclusively for its spatial expression during SE, than the regulatory sequences of AtSERK2 gene.…”
Section: Structural Evolution Of Se-specific Promoter Regions Of Serksupporting
confidence: 63%
See 1 more Smart Citation
“…It is thus clear that ANT transcription factors are regulated by auxin gradient suggested for auxin-mediated regulation of ANT transcription factor in SE. The ANT is part of a complex and robust molecular system that coordinates patterning signals and cellular proliferation through embryo development [58]. This data indeed provide support for the structural changes in the regulatory sequence of AtSERK1 gene evolved exclusively for its spatial expression during SE, than the regulatory sequences of AtSERK2 gene.…”
Section: Structural Evolution Of Se-specific Promoter Regions Of Serksupporting
confidence: 63%
“…AINTEGUMENTA is an AP2-like ethylene responsive transcription factor, a family of proteins involved in ethylene signal transduction recognizing and binding to the DNA consensus sequence 5'-CAC[AG]N[AT] TNCCNANG-3' [58]- [61]. The trans-factor ANT has been reported for its important role in the cellular fate deciding processes throughout the development of ovule and female gametophyte; and even upto embryogenesis.…”
Section: Structural Evolution Of Se-specific Promoter Regions Of Serkmentioning
confidence: 99%
“…Previously published mutants and marker lines used in this study include seu-3 and seu-4 (Pfluger and Zambryski, 2004), ga1 (Sun and Kamiya, 1994), scr-3, shr-2, and SHR::SHR-GFP (Nakajima et al, 2001), SCR::H2B-YFP (Heidstra et al, 2004), scl3, SCL3::GUS, and SCL3::SCL3-GFP , CYCD6;1::GFP-GUS (Sozzani et al, 2010), and SEU::SEU-GFP (Azhakanandam et al, 2008). Primers used for mutant genotyping are listed in Supplemental Table S1.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…nA, No antibody; Ab, GFP antibody. Azhakanandam et al, 2008;Bao et al, 2010;Nole-Wilson et al, 2010;Lee et al, 2014). Interestingly, although SEU does not appear to possess a recognizable DNA-binding motif, it was shown by chromatin immunoprecipitation (ChIP) to associate with cis-regulatory elements located in the second intron of the floral homeotic gene AGAMOUS (AG; Sridhar et al, 2006) and with cisregulatory elements of miR172 genes (Grigorova et al, 2011).…”
mentioning
confidence: 99%
“…This agrees with the results shown in Figure 2, as the expression pattern of this gene was reduced by 70% when buds were next to the anthesis and therefore when all gametic structures had been generated. In A. thaliana, functional analysis indicated that SEUSS plays other roles in flower development, specifically in the carpel margin meristems, a vital meristematic structure located at the margins of the fused carpels and that gives rise to several structures in the female reproductive system, including the eggs (Franks et al, 2002;Azhakanandam et al, 2008;Grigorova et al, 2011;Kamiuchi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%